Introduction of Conditional Probability with the Relative Frequency Approach: Focus on the Use of the Frequency Tree Diagram and Simulation - Inyong Choi (Korea Society of Educational Studies in Mathematics, 2021)
The purpose of this study is to propose and discuss the pedagogical idea of introducing conditional probability with the relative frequency approach. This study developed a learning activity and simulation using the frequency tree diagram and implemented them. The first-year high school students (n=14) were able to construct the concept of conditional probability through a frequency perspective of sequentially obtaining the conditional relative frequency, the limit of the relative frequency, and the theoretical probability. The implications for teaching and curriculum were presented.